Candida albicans biofilm: formation and antifungal agents resistance - Wibawa, Tri (Universitas Gadjah Mada, 2012)
Candida sp are the most common fungal pathogens causing fatal health care associated infections.Among the genus of Candida, Candida albicans is the most frequent species isolated frompatients. The notorious C. albicans infection is the ability of this dimorphic fungus to formbiofilm. Biofilm has been pointed as a dynamic phenotypic switching in bacteria and fungi,which may result in higher morbidity and mortality in human beings. This review addresses thebasic explanation of biofilm formation which is characterized by the antifungal agents resistance.The factors that influence C. albicans biofim formation and antifungal agents resistance arediscussed.Key words: Candida sp â antifungal â resistance â biofilm - pathogenecity